3(n+4)=-3(4+n)

Simple and best practice solution for 3(n+4)=-3(4+n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(n+4)=-3(4+n) equation:


Simplifying
3(n + 4) = -3(4 + n)

Reorder the terms:
3(4 + n) = -3(4 + n)
(4 * 3 + n * 3) = -3(4 + n)
(12 + 3n) = -3(4 + n)
12 + 3n = (4 * -3 + n * -3)
12 + 3n = (-12 + -3n)

Solving
12 + 3n = -12 + -3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3n' to each side of the equation.
12 + 3n + 3n = -12 + -3n + 3n

Combine like terms: 3n + 3n = 6n
12 + 6n = -12 + -3n + 3n

Combine like terms: -3n + 3n = 0
12 + 6n = -12 + 0
12 + 6n = -12

Add '-12' to each side of the equation.
12 + -12 + 6n = -12 + -12

Combine like terms: 12 + -12 = 0
0 + 6n = -12 + -12
6n = -12 + -12

Combine like terms: -12 + -12 = -24
6n = -24

Divide each side by '6'.
n = -4

Simplifying
n = -4

See similar equations:

| 5[7-5(6-q)]-7=7[(7q-6)+4]-50 | | (x^4-2.3x^3+6)(x^4-2.3x^3+6)=0 | | 4-6lnx=y | | -2x=2y-4 | | 4x+11=4x-21 | | -9(x-1)=-8x-6 | | 3(2x-2)=5(x+4) | | 8+2x=-x+35 | | 8y-2=9y-2y | | 3r-5r+r+8= | | 50/1x=3 | | 5x+10=64-x | | 3x^6+15x^4-12x^2=0 | | s-9=11 | | -5+4x+3x=-33 | | log(4)(x+2)=3 | | 4(-6+x)=16 | | 3(x+8)+5x=8x-24 | | 6(3x+8)=228 | | -6x+2y=34 | | 3(5x+9)=-37+19 | | 6(-9-x)=-24 | | 2(2x)=32 | | -8(8x-6)=-6x-228 | | -2x+2=7x+65 | | 7m(2m-12)=0 | | -1+6x=-3x+8 | | 2(4x+2)+9x= | | 50/x=3 | | 90=3x+5x-6 | | ln(x)-ln(4)=0 | | (7+5x)-5x= |

Equations solver categories